2016
DOI: 10.1103/physreva.93.033653
|View full text |Cite
|
Sign up to set email alerts
|

Postquench dynamics and prethermalization in a resonant Bose gas

Abstract: We explore the dynamics of a resonant Bose gas following its quench to a strongly interacting regime near a Feshbach resonance. For such deep quenches, we utilize a self-consistent dynamic field approximation and find that after an initial regime of many-body Rabi-like oscillations between the condensate and finite-momentum quasiparticle pairs, at long times, the gas reaches a pre-thermalized nonequilibrium steady state. We explore the resulting state through its broad stationary momentum distribution function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…In order to predict contact dynamics from a three-body wave function, it is necessary to choose initial conditions such that Eqs. (10) and (11) matches the prepared manybody system under study. In this work, we consider an ultracold Bose gas prepared as either a BEC or an ideal thermal Bose gas.…”
Section: A Initial Conditionsmentioning
confidence: 74%
“…In order to predict contact dynamics from a three-body wave function, it is necessary to choose initial conditions such that Eqs. (10) and (11) matches the prepared manybody system under study. In this work, we consider an ultracold Bose gas prepared as either a BEC or an ideal thermal Bose gas.…”
Section: A Initial Conditionsmentioning
confidence: 74%
“…Our estimate of η is close to the predictions for a prethermal state in Refs. [22,24], but the exponential n k k 3 n has (to our knowledge) not been theoretically predicted. Explaining this experimental observation may require explicitly considering the quench away from unitarity.…”
mentioning
confidence: 76%
“…Time-resolved studies of the single-particle momentum distribution in Ref. [13] revealed that the theoretically predicted prethermal state [14][15][16] transitions to steady state prior to being overcome by heating. Although * s.musolino@tue.nl these findings, combined with studies of loss dynamics in Refs.…”
Section: Introductionmentioning
confidence: 98%